Leaching Behaviour of Bifenthrin And I-Cyhalothrin in Sandy Loam Soil (Global Journal of Science Frontier Research, 2012)
The purpose of this study was to determine the leaching behaviour of pyrethroids. Now days pyrethroids are applied largely in India, creating the need to evaluate potential leaching of pyrethroids. Thus leaching of bifenthrin and λ -cyhalothrin in sandy loam soil was evaluated under laboratory conditions with simulated rainfall of 300 mm. Bifenthrin was applied at 2 and 4 μg while λ -cyhalothrin was applied at 2 and 4 μg on soil columns, respectively. Maximum concentration of bifenthrin and λ -cyhalothrin was recovered from 0-5 cm depth in the soils. Results indicated the low mobility of both the insecticides under saturated moisture condition that may be significant in terms of ground water contamination Now a days pyrethroids .
Keywords: Leaching; bifenthrin; λ-cyhalothrin; residues; sandy loam soil; column